Komunikasi Orang Tua Membangun Karakter Anak dalam Perspektif al-Qur'an dan Sunnah Nabi - Marzuki (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This research needs to be done to find forms of parental communication in building children's character. Character communication must be based on the principle of identifying characters comprehensively including thoughts, feelings and behavior. Religion has a big part in the process of forming the character of children. There is a positive relationship between religion and the formation of children's character. There are also many people who have religious knowledge in a cognitive way but it is not reflected in their behavior. This research uses content analysis method with a thematic interpretation approach to describe the value of parental communication in the Koran on the formation of children's character. The results showed that in the Qur'an there is an explanation of the communication of children and parents in character building.